A new approach for the management of Escherichia coli and Klebsiella pneumonia by using cefixime-based bionanocomposite films. Issue 1 (31st December 2022) - Alotaibi, Badriyah Shadid; Ashames, Akram; Buabeid, Manal; Masood, Momina; Mir, Sadullah; Murtaza, Ghulam
Abstract: Purpose: The aim of this study was to assess the antibacterial potential and ex vivo skin permeation kinetics of cefixime from bionanocomposite films. Methods: The films were prepared by solvent casting method by using chitosan and starch. The fabricated films were tested for their antibacterial potential against three bacteria i.e. Escherichia coli, Klebsiella pneumonia, and Acetobacter aceti . In vitro permeation studies of cefixime from the films across rat skin was conducted using Franz diffusion cell. Results: The highest antibacterial effect was exhibited by F5 formulation (non-irradiated film) against Escherichia coli and Klebsiella pneumonia ; however, antibacterial activity of the films was significantly ( p < 0.05) reduced after their irradiation. F5 formulation showed the highest cumulative amount of permeated drug after 24 h, while F1 (100% chitosan) showed the lowest amount of permeated drug. Non-Fickian diffusion (anomalous) was the main mode of drug release from all films. The cross-linking of films by γ-radiations improved their mechanical properties. The percentage swelling ratio was the highest in non-irradiated films having a polymeric blend (50:50). Water uptake of irradiated films was appreciably reduced as compared to non-irradiated films. Conclusion: The synthesized bionanocomposites are promising therapeutic moieties which not only improve drug permeability across but also ameliorates antibacterial potential of cefixime.